Women’s Labor Force Success in Hong Kong - Widodo Widodo (Journal of Islamic World and Politics, 2021)
International migration occurs because population growth does not match the job opportunities and availability. This issue has increased labor migration abroad. International migration as a workforce is dominated by female migrant workers or Tenaga Kerja Wanita (TKW). Women in their development want to actualize themselves by having transitional roles as workers who actively earn money for their families. During this time, news and research are still around the protection and problems TKI / TKW has experienced. Only a few studies have focused on the TKI / TKW’s success during their work. This research is qualitative using the textual study method by analyzing secondary data from various related literature and former TKW interviews. Empirical data showed that the factors leading to Hong Kong’s success were caused by the Hong Kong and Indonesian governments’ policies. They protected the workers’ rights and support to self-actualize, and female workers began to join the organization. Thus, women had more insight, freedom, and confidence to work in Hong Kong.